1991
DOI: 10.1007/bf00190527
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of KNO3 and salinity on yield and chemical composition of lettuce and Chinese cabbage

Abstract: The effect of N and K nutrition on the salt tolerance of lettuce (Lactuca sativa L. cv. 'Salinas') and Chinese cabbage (Brassica campestris L., Pekinensis cv. Kazumi) was evaluated in three greenhouse experiments under a controlled aero-hydroponic system of cultivation. Three levels of KNO3 (1, 5 and 10 mM) were tested in all the experiments with rapidly circulated saline and nonsaline nutrient solutions. Two experiments, carried out between January and March 1989, with lettuce (Exp. I) and Chinese cabbage pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 14 publications
1
19
1
1
Order By: Relevance
“…In contrast to the effect of Cl À on NO À 3 uptake, others have reported that increased NO À 3 in the substrate decreased Cl À uptake and accumulation in numerous annual horticultural crops (Bernstein et al, 1974;Kafkafi et al, 1982;Feigin et al, 1987;Martinez and Cerda Â, 1989). This effect is particularly relevant in tree or vine crops that are prone to Cl-toxicity.…”
Section: Nitrogenmentioning
confidence: 92%
See 2 more Smart Citations
“…In contrast to the effect of Cl À on NO À 3 uptake, others have reported that increased NO À 3 in the substrate decreased Cl À uptake and accumulation in numerous annual horticultural crops (Bernstein et al, 1974;Kafkafi et al, 1982;Feigin et al, 1987;Martinez and Cerda Â, 1989). This effect is particularly relevant in tree or vine crops that are prone to Cl-toxicity.…”
Section: Nitrogenmentioning
confidence: 92%
“…Despite the lack of evidence indicating that N applied to saline soils or media above a level considered optimal under non-saline conditions improves plant growth or yield, a number of laboratory and greenhouse studies have shown that salinity can reduce N accumulation in plants (Cram, 1973;Pessarakli and Tucker, 1988;Feigin et al, 1991;Pessarakli, 1991;Al-Rawahy et al, 1992). This is not surprising since an increase in Cl À uptake and accumulation is often accompanied by a decrease in shoot-NO À 3 concentration.…”
Section: Nitrogenmentioning
confidence: 99%
See 1 more Smart Citation
“…Rameshwaran et al [12] investigated effects of different irrigation regimes with salinity treatments using a drip irrigation system for two pepper varieties in the greenhouse in Antalya, Turkey. Feigin et al [17] tested the response of lettuce and Chinese cabbage to the combination of a wide range of salinity and potassium nitrate levels in the greenhouse using an aero-hydroponic system. Garrido et al [18] evaluated physiological, phytochemical, and structural changes in lettuce by salt stress in a soilless system.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in agreement with the observations of Kaya et al 26 . According to Feigin et al 27 and Grattan and Grieve…”
Section: Discussionmentioning
confidence: 99%